Peran Involvement Sebagai Variabel Pemoderasi Model Loyalitas Pelanggan - Setyanta, Budi (Fakultas Ekonomi dan Bisnis, UNTAN, 2018)
This research aims to identify the role of involvement as a moderating variable in the model of customer loyality. The population in this study is the Xiaomi smartphone users in Yogyakarta. Data is collected through survey method that is guided by questionnaire. The data samples are 200 respondents to eligible the data analysis by structural equation modeling. The results indicate that the involvement moderates the effect of perceived quality, perceived price and after-sales service towards customer satisfaction.. Besides, the result is the involvement moderates the effect of customer satisfaction on customer loyalty. The results are used to develop strategies to effectively increase customer loyalty by designing a stimulus to increase customer loyalty considering the level of customer involvement.